Analisis Penyebab Tidak Digunakannya Sistem Informasi Manajemen Puskesmas (Simpus) dalam Penerimaan Pasien Rawat Jalan di Puskesmas Kalimas Kecamatan Randudongkal Kabupaten Pemalang - Linda Ida Tiara; Subinarto Subinarto (Poltekkes Kemenkes Semarang, 2019)
Simpus is a system to improve the quality of puskesmas management and as a supporter in the smooth management of health information in Puskesmas. Based on the preliminary study of Kalimas Puskesmas in the process of admission an outpatient not use Simpus and still done manually The purpose of this research is to analyze the causal factors of the management Information System Puskesmas (Simpus) seen from the aspects of human resources, supporting materials, infrastructure facilities, implementation and fund source.The type of research used is descriptive research with qualitative approach. Methods of collection observation data and interview. Presentation of the data to be done ie in the form of fish bone diagram that contains about the factors of the cause of the not used SimpusThe results of the qualification study and the number of available medical record officers are not eligible. There has been no obligation from the Department of Health to use Simpus. Simpus from the Department of Health is integrated with Disduccapil and automatic numbering, the medical record number will differ from the number in the Family folder. There is only one computer in the registration. There has been no budget for such infrastructures for computers. Conclusion is not used Simpus seen from the aspect of human resources, the way of implementation, supporting materials, infrastructure and sources of funds have not been in accordance